THEATRICAL ART AS A MEANS OF DEVELOPING INTERPERSONAL SKILLS IN PUPILS WITH AUTISM SPECTRUM DISORDERS - Perevorska Olena; Prohodko Tetyana; Kobzіeva Iryna (Alfred Nobel University Publisher, 2024)
The article deals with the problem of the effectiveness of correctional work of higher education students with younger students with autism spectrum disorders. The aim of the article is to theoretically substantiate the problem and highlight the results of an empirical study on identifying the level of development of interpersonal interaction skills in primary school children with autism spectrum disorders through the means of theatrical art. The theoretical analysis of the problem has shown that the acquisition of experience of interaction, and skills of contact with children is recognized as one of the priority directions of personality development at the primary school age. In science, communication is considered as the interaction and establishment of contacts between individuals, which results in influencing each other, exchanging information, choosing a certain direction of joint action, as well as perceiving and understanding the interlocutor. It was determined that the artistic and communicative experience gained at the primary school age is a guarantee not only of the child's general cultural development, but also of his or her liberation, confidence, and personal activity in later life. The emphasis was placed on the fact that theatrical activity proves to be an effective means of socialisation of primary schoolchildren, as it promotes comprehension of the moral implications of a literary work and participation in the game. This form of activity creates favourable conditions for development, focused on the holistic development of the personality of a child with ASD, activation of his/her creativity, and key mental processes. It is emphasised that the solution to the problem will be the implementation of a correctional and developmental program by higher education students aimed at developing interpersonal skills in primary school children with autism spectrum disorders. Under our supervision, students of Oles Honchar Dnipro National University conducted a study of the level of development of interpersonal skills in primary school children with autism spectrum disorders. The study involved primary school children with autism spectrum disorders in grades 1-A: 13 children - experimental group, and 1-B: 14 children - control group. The results of the study allowed higher education students to conclude that the development of interpersonal skills in primary school children with autism spectrum disorders can be successful under conditions of specially organised, systematised, and regular classes in the correctional and developmental program «Young Actors». The empirical study applied methods and strategies for implementing theatrical classes in the educational process with children with autism spectrum disorders. The use of theatrical art helps to improve communication skills, emotional understanding and social adaptation in children with autism spectrum disorders. The results obtained indicate the effectiveness of the correctional work of higher education students with children with autism spectrum disorders. Conclusions have been drawn regarding the effectiveness of the corrective developmental program in shaping interpersonal interaction skills in children with autism spectrum disorders through theatrical art. The practical results of the work can be useful for teachers, psychologists and parents who work with this category of children and seek to improve their quality of life and social interaction. In addition, the educational environment will contribute to social adaptation and the development of interaction skills in children with autism spectrum disorders.